FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PNEUMONIA PADA BALITA - Rinawati, Rinawati; Khresna Dewi, Vonny; Tunggal, Tri; Rafidah, Rafidah (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: According to the World Health Organization (WHO), pneumonia is the leading cause of death in children under five worldwide, the